COMBINATION OF PROPOFOL/REMIFENTANIL VS SEVOFLURANE/REMIFENTANIL FOR MAINTENANCE OF ANAESTHESIA FOR INTRACRANIAL SURGERY COMPARATIVE STUDY - Dr. Eman Sahib Mahdi; Dr. Enaam Yahya Ebraheem; DR. Orooba Mezher Hasan (Scholar Express Journals, 2023)
Propofol and sevoflurane are suitable agents for maintaining anesthesia during neurosurgical procedures. We prospectively compared these agents in combination with remifentanil, a short-acting opioid
Keywords: Intravenous anesthetics; propofol; volatile anesthetics